Investigation of Different Carbon Materials with Different Coating Methods as Micro Porous Layer for Proton Exchange Membrane Fuel Cells - Liu, Yu-Hsu; Jao, Ting-Chu; Tzeng, Wei-Jen; Jung, Guo-Bin; Sun, Shih-Yuan; Wang, Cheng-Tang (Journal of Technology Innovations in Renewable Energy, 2013)
In this work, two types of carbon - Vulcan XC-72R, and vapor-grown carbon fiber (VGCF, 7μm in length and 100 nm in diameter) were investigated as materials composing a micro porous layer (MPL). These carbon materials were either sprayed or doctor bladed on commercial carbon paper (GDS 340, CeTech Co., Ltd., Taiwan) to form an MPL with various carbon loadings and various polytetrafluoroethene (PTFE) contain ratio. All of the home-made GDLs were assembly with commercial catalyst coated membranes (CCMs, General Optics Corp., Taiwan) for fuel cell performance test. All of the membrane electrode assembly (MEA) samples were investigated by the polarization curve and Electrochemical Impedance Spectroscopy (EIS).